ABA Alleviates Uptake and Accumulation of Zinc in Grapevine (Vitis vinifera L.) by Inducing Expression of ZIP and Detoxification-Related Genes - Song, Changzheng; Yan, Yifan; Rosado, Abel; Zhang, Zhenwen; Castellarin, Simone Diego (Frontiers in Plant Science, 2019)
Abscisic acid (ABA) is a plant hormone that can mitigate heavy metal toxicity. Exogenous ABA and ABA mimic 1 (AM1) were applied to study the influence on Zn uptake and accumulation in Vitis vinifera L. cv. Merlot seedlings exposed to excess Zn. The seedlings were treated with either normal or excess levels of Zn in combination with applications of ABA and AM1. Excess Zn exposure resulted in decreased lateral root length, decreased photosynthesis, elevated uptake, and accumulation of Zn in roots, trunks, and stems, decreased jasmonic acid content in roots and leaves, and induced the expression of Zn transportation- and detoxification-related genes. Remarkably, in the presence of toxic amounts of Zn, the exogenous application of ABA, but not of AM1, reduced the uptake and accumulation of Zn in roots and induced higher expression of both ZIP genes and detoxification-related genes in root and leaf. These results indicate that exogenous ABA enhances the tolerance of grape seedlings to excess Zn and that AM1 is not a suitable ABA mimic compound for Zn stress alleviation in grapes.